2019
DOI: 10.21608/ejchem.2019.15173.1919
|View full text |Cite
|
Sign up to set email alerts
|

Graphene: Structure, Synthesis, and Characterization; a brief review

Abstract: I N 2004, Andrei Geim and Kostya Novoselov used a simple technique to separate graphene layer from graphite. They were awarded the Nobel Prize in Physics in 2010. After this, the publications of graphene have been increasing year after year and have emerged as the most popular topic in the research field which indicates the importance of graphene research. Due to unique properties of graphene, it can be considered as promising material for various applications in the fields of physics, chemistry, material scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Among the shortcomings of graphene synthesis procedures are multiple synthesis stages, a lengthy synthesis time, limited stability, stacking, and poor ease of processing for mass manufacturing. [ 149–152 ]…”
Section: Sensor Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the shortcomings of graphene synthesis procedures are multiple synthesis stages, a lengthy synthesis time, limited stability, stacking, and poor ease of processing for mass manufacturing. [ 149–152 ]…”
Section: Sensor Applicationmentioning
confidence: 99%
“…Among the shortcomings of graphene synthesis procedures are multiple synthesis stages, a lengthy synthesis time, limited stability, stacking, and poor ease of processing for mass manufacturing. [149][150][151][152] Nonaka et al investigated the problem of graphene restacking by synthesizing a CG structure using manganese ferrite NPs in a single step. They aimed to develop a new form of CG fully decorated with manganese ferrite NPs for H 2 O 2 sensing.…”
Section: Chemical Sensorsmentioning
confidence: 99%
“…So, GO was used as a starting material or precursor for various applications. [15] The biocompatibility of GO allows its application in an emerging field such as anticancer therapy, biofunctionalization of protein, gene, and small molecular drug delivery. [16] Nanocomposites combine the advantages of two or more nanomaterials, [13,17,18] so, many studies were reported on the preparation, advantage, and applications of GO-based nanocomposites.…”
mentioning
confidence: 99%
“…Two-dimensional (2D) materials have covered a wide range of specifications and applications , due to their various features in many fields such as electronics, optoelectronics, conductivity, and energy storage. Because of success in graphene and graphene-based investigations, , 2D materials, particularly honeycomb structures, have generally gained more and more attention for designing next-generation devices. In 2D materials, the physical and chemical properties strongly and consistently depend on geometric properties, leading to the necessity and significance of solving structural problems.…”
Section: Introductionmentioning
confidence: 99%